2022
DOI: 10.3390/ijerph20010548
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Affecting Mathematics Teachers’ Well-Being and Stress Levels: An Extended Engagement Theory

Abstract: The mathematics teachers’ profession often has many challenges. It also occupies important positions at the K-12 education level, in which mathematics knowledge is the basis of all scientific fields. This tends to cause high-stress levels and a negative effect on well-being. Mathematics teachers’ well-being has been less examined, and therefore this study aims to determine the factors affecting mathematics teachers’ well-being and stress levels. The 210 data points collected from Chinese mathematics teachers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…Based on the result of the review, it could be observed that only one selected article fosters a theme on the mathematic teachers' well-being while two articles are on teachers' performance. It was reported that Teachers' well-being was significantly reduced by increasing stress levels (Jian et al, 2023). This shows that increasing level of stress reduces the well-being of mathematics teachers.…”
Section: Work-life Balance Teachers' Well-being and Performancementioning
confidence: 90%
See 2 more Smart Citations
“…Based on the result of the review, it could be observed that only one selected article fosters a theme on the mathematic teachers' well-being while two articles are on teachers' performance. It was reported that Teachers' well-being was significantly reduced by increasing stress levels (Jian et al, 2023). This shows that increasing level of stress reduces the well-being of mathematics teachers.…”
Section: Work-life Balance Teachers' Well-being and Performancementioning
confidence: 90%
“…For instance, Mujtaba et al (2013) reported that teachers with appropriate stress-coping mechanisms and access to professional and personal support could produce desirable teaching output. Also, Jian et al (2023) reported that enhancing teachers' well-being significantly reduced stress levels. More so, Fisher & Royster (2016) submitted that different schools have different inherent stress levels and that as teachers, they used several mechanisms for reducing stress, while Cheng-Lin et al (2020) reported that the adverse effect of stress and job burnout is strengthened by both employee agility and Leader-Member Change Quality (LMCQ).…”
Section: Work-life Balance and Stress Among Mathematics Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a certain range of learning time, there is a positive relationship between student engagement in learning and attitudes toward school (learning activities) and subjective well-being (sense of belonging to school), but after a threshold, there is a negative effect. The decline in students’ well-being and subjective learning attitudes affects students’ learning outcomes negatively [ 42 ], which in turn affects student academic achievement negatively. It has been shown that excessive learning time after school not only negatively affects students’ academic performance directly but also affects academic performance through non-cognitive factors such as students’ emotions and attitudes.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…An important predictor of academic success and indicator of educational quality, learning engagement has recently attracted considerable research attention. It is positively related to learners’ academic achievement and experience of attendance as well as deep learning, reduced dropout rates, increased learner satisfaction with school, future career development levels, wellbeing, and critical thinking skills ( Howell, 2009 ; Trenholm et al, 2019 ; Jian et al, 2022 ). However, in China as in other contexts, insufficient engagement in learning among university students is a widespread phenomenon.…”
Section: Introductionmentioning
confidence: 99%